2017
DOI: 10.1111/mpp.12514
|View full text |Cite
|
Sign up to set email alerts
|

Infection assays in Arabidopsis reveal candidate effectors from the poplar rust fungus that promote susceptibility to bacteria and oomycete pathogens

Abstract: SUMMARYFungi of the Pucciniales order cause rust diseases which, altogether, affect thousands of plant species worldwide and pose a major threat to several crops. How rust effectors-virulence proteins delivered into infected tissues to modulate host functionscontribute to pathogen virulence remains poorly understood. Melampsora larici-populina is a devastating and widespread rust pathogen of poplar, and its genome encodes 1184 identified small secreted proteins that could potentially act as effectors. Here, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
69
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 42 publications
6
69
1
Order By: Relevance
“…Necrotrophic pathogens utilize many secreted PCWDEs to overcome the barrier of the plant cell wall. EffectorP predicts some secreted proteins with enzymatic domains as effectors, such as the Fusarium graminearum xylanase XylA, which has the ability to induce necrosis in wheat independent of its enzymatic activity (Table ) (Belien et al ., ; Sella et al ., ; Sperschneider et al ., ). However, EffectorP has been trained on effectors that predominantly lack recognizable functional domains and interfere with host processes in different ways from PCWDEs which act on the plant cell wall.…”
Section: Resultsmentioning
confidence: 99%
“…Necrotrophic pathogens utilize many secreted PCWDEs to overcome the barrier of the plant cell wall. EffectorP predicts some secreted proteins with enzymatic domains as effectors, such as the Fusarium graminearum xylanase XylA, which has the ability to induce necrosis in wheat independent of its enzymatic activity (Table ) (Belien et al ., ; Sella et al ., ; Sperschneider et al ., ). However, EffectorP has been trained on effectors that predominantly lack recognizable functional domains and interfere with host processes in different ways from PCWDEs which act on the plant cell wall.…”
Section: Resultsmentioning
confidence: 99%
“…We collected 13 gene sets from the literature that were labelled as containing effector candidates based on their induction during infection as well as other criteria (Table 4). For example, a study by Germain et al (2016) identified 16 candidate effectors from 1,184 small, secreted Melampsora larici-populina proteins. These 16 candidates were selected based on their expression in a haustoria-specific cDNA library and the transcriptome of laser microdissected, rust-infected poplar leaves as well as their small size of less than 300 aas.…”
Section: Resultsmentioning
confidence: 99%
“…This gene is part of a Melampsoraceae family and other members were shown to possess a transit peptide to target chloroplasts in plant cells. Sixteen other M. larici-populina candidates were assayed in A. thaliana through stable expression of GFP fusion to determine their subcellular localization (Germain et al, 2017). Three candidates showed an accumulation in plasmodesmata, chloroplasts and cytoplasmic bodies, respectively; 11 promoted Hyaloperonospora arabidopsidis growth in planta, and five promoted P. syringae growth in planta.…”
Section: Effectoromics Of the Poplar Rust Fungus M Larici-populinamentioning
confidence: 99%
“…Three candidates showed an accumulation in plasmodesmata, chloroplasts and cytoplasmic bodies, respectively; 11 promoted Hyaloperonospora arabidopsidis growth in planta, and five promoted P. syringae growth in planta. Three candidates promoted both oomycete and bacterial growth and may be considered as virulence factors (Germain et al, 2017). Investigations conducted in two different heterologous systems highlighted 11 poplar-rust candidate effectors with specific localization and/or plant protein interactors (Table 1).…”
Section: Effectoromics Of the Poplar Rust Fungus M Larici-populinamentioning
confidence: 99%
See 1 more Smart Citation